2016
DOI: 10.1590/s1984-82502016000200012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the functionality of bread loaves prepared with quinoa flakes through biological tests

Abstract: The aim of this study was to evaluate quinoa flakes and bread prepared with the pseudocereal with regard to nutritional aspects by determining chemical composition, content of tocopherols and fatty acid composition as well as to possible beneficial effects in Wistar rats given commercial feed supplemented or not with quinoa flakes and cholesterol. The following parameters were determined: weight gain, food intake, liver weight, fat in liver and lipid profile in blood and liver. The results showed that processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The main source of nitrogen in quinoa slurries are aminoacids, ammonium ions and di, tri-peptides [21]. It was reported that total aminoacid content in quinoa is higher than in barley, rice or wheat [2]. Next to nitrogen sources, minerals, and especially key metal ions, are important determinants of yeast performance.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The main source of nitrogen in quinoa slurries are aminoacids, ammonium ions and di, tri-peptides [21]. It was reported that total aminoacid content in quinoa is higher than in barley, rice or wheat [2]. Next to nitrogen sources, minerals, and especially key metal ions, are important determinants of yeast performance.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that metal ions like Mg 2+, K + , Ca 2+, and Zn 2+ have an impact on yeasts during brewing [13]. As reported by a large body of research, the main minerals in quinoa are potassium, phosphorus, and magnesium, while calcium and zinc are also present in relative high amounts [2]. Even if, quinoa was the main flour in preferment, amaranth flour also sustained the microbial growth and activity due to its rich composition in nitrogen compounds, minerals, vitamins and fermentable sugars [4].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations